International Multicenter, Myopic and Myopic Astigmatism Femto LASIK, Customized by Automated Ray-Tracing Ablation Profile Calculation: A Postmarket Study - Kanellopoulos AJ; Maus M; Bala C; Hamilton C; Lemonis S; Jockovich ME; Khoramnia R (Clinical Ophthalmology, 2024)
Anastasios John Kanellopoulos,1,2,* Matthias Maus,3,* Chandra Bala,4,* Cody Hamilton,5,* Sissimos Lemonis,6,* Maria Elena Jockovich,5,* Ramin Khoramnia7,* 1LaserVision Ambulatory Surgical Unit, Athens, Greece; 2Department of Ophthalmology, NYU Grossman School of Medicine, New York City, NY, USA; 3Sehkraft Augenzentrum, Köln, Germany; 4PersonalEyes, Sydney, NSW, Australia; 5Alcon Vision, LLC, Fort Worth, TX, USA; 6Alcon Deutschland GmbH, Freiburg, Germany; 7Department of Ophthalmology, University of Heidelberg, Heidelberg, Germany*These authors contributed equally to this workCorrespondence: Anastasios John Kanellopoulos, LaserVision Ambulatory Surgical Unit, An Thocha 17, Athens, 115 21, Greece, Tel +30 (210) 7472777, Fax + 30 (210) 7472789, Email ajkmd@mac.comPurpose: To assess the safety and efficacy of a customized ablation treatment (InnovEyes) to correct myopia and myopic astigmatism with femtosecond laser-assisted in situ keratomileusis (Femto LASIK).Patients and Methods: In this prospective, nonrandomized, multicenter study, 113 patients (225 eyes) with preoperative myopia less than − 9.0 diopters (D) and astigmatism 0 to − 4.0 D (based on InnovEyes refraction) underwent wavefront, tomography, and biometry assessment using a single diagnostic device (InnovEyes sightmap). These data were imported and used unmodified by the InnovEyes algorithm to automatically calculate and optimize correction of lower- and higher‑order aberrations (HOAs) treated by the EX500 ablation profile. Visual acuity, refractive error, HOAs, and patient satisfaction were evaluated over 3 months.Results: A total of 106 patients (212 eyes) completed the study and were included in the analysis. Mean preoperative manifest refraction spherical equivalent (MRSE) was − 3.38± 1.76 D. At Month 3, uncorrected distance visual acuity was 20/20 or better in 208/212 (98.1%) eyes, and it was the same as, or better than, the preoperative best-corrected distance visual acuity (CDVA) in 162/212 (76.4%) eyes; 76/212 (35.8%) eyes gained ≥ 1 line of CDVA. MRSE was within ± 0.5 D in 195/212 (92.0%) eyes. Additionally, 201/209 (96.2%) eyes had no change (defined as a change between − 0.1 μm and 0.1 μm, inclusive) in HOAs, and 105/106 (99.1%) patients reported to be satisfied with the results.Conclusion: Customizing ray-tracing Femto LASIK with this platform appeared safe and effective in correcting myopic astigmatism and also achieved a significant percentage of eyes gaining lines of vision, potentially by addressing HOAs, along with a consistently high level of patient satisfaction.Keywords: myopic astigmatism, higher-order aberrations, manifest refraction spherical equivalent, corrected distance visual acuity